A hole injection monolayer enables cost-effective perovskite light-emitting diodes. Issue 8 (31st January 2023) - Zhang, Congyang; Mariotti, Silvia; Ono, Luis K.; Ding, Chenfeng; Mitrofanov, Kirill; Zhang, Caiyi; Yuan, Shuai; Ji, Penghui; Zhang, Jiahao; Wu, Tianhao; Kabe, Ryota; Qi, Yabing
Abstract : Cost-effective fabrication of efficient metal halide perovskite light emitting diodes are realized by using a hole injection monolayer, which is demonstrated to be highly effective for hole injection and radiative recombination. Abstract : Developing cost-effective fabrication is one of the key steps for metal halide perovskite light emitting diodes (PeLEDs) toward their future commercialization and industrial applications. Considering the low material consumption, upscalable processing and energy level offset tunability of the surface anchored monolayer, we proposed a [2-(9 H -carbazol-9-yl)ethyl]phosphonic acid, 2PACz-based hole injection monolayer (HIML) for the cost-effective fabrication of efficient PeLEDs. On the basis of the systematic surface science study and characterization, we elucidate the effect of the 2PACz molecular layer on the work function engineering of ITO, energetic alignment and hole injection between ITO and the perovskite emission layer, and the radiative recombination of the perovskite layer at the bottom interface. In particular, our thickness-dependent UPS measurement results suggest that the molecular dipole of 2PACz is the main contributor for the work function change of ITO. Finally, by demonstrating efficient LEDs with blue emission and enlarged device area, we verified the universality of the HIML-based strategy. This study highlights the great potential of the HIML for cost-effective PeLEDs, which can help translate perovskite light emission technologies toward the commercial level in the future.